Camera Self-Calibration in the AUV Monocular Vision Navigation and Positioning - GAO Jun-chai; LIU Ming-yong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Camera calibration is essential to obtain 3D information from 2D image, for underwater camera self-calibration, because the linear model can not accurately describe the imaging geometry of real cameras, the underwater camera nonlinear model and its calibration method are studied. According to the relationship between underwater and air in the camera focal length, principal point and no vertical factors, the underwater camera imaging geometry is modeled. Underwater camera nonlinear imaging geometry is modeled with the radial distortion. The constraint equation of the nonlinear model parameters are set up with linear imaging model and fundamental matrix of the matching points, which realize the camera self-calibration of nonlinear parameters. For the linear parameters of the camera, with the principal point and no vertical factor known, the self calibration of the focal length can be realized with two images, according to the Kruppa equation. Simulation and real image experiments show that the method given is feasible, and has certain practical value. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3726